Downside and upside risk spillovers between exchange rates and stock prices - Reboredo, Juan C.; Rivera-Castro, Miguel A.; Ugolini, Andrea (Journal of Banking & Finance, 2016)
We examined downside and upside risk spillovers from exchange rates to stock prices and vice versa for a set of emerging economies. We characterized the dependence structure between currency and stock returns using copulas and computed downside and upside value-at-risk and conditional value-at-risk. We documented a positive relationship between stock prices and currency values in emerging economies with respect to the US dollar and the euro, with downside and upside spillover risk effects transmitted both ways. Finally, we also documented asymmetries in upside and downside risk spillovers and asymmetric differences in the size of risk spillovers when the domestic currency values against the US dollar and the euro. Our results, consistent with flight-to-quality phenomena, have implications for downside and upside risk management of international investor portfolios in emerging markets.